2005
DOI: 10.2337/diacare.28.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Hyperglycemia and Cognitive Performance Among Adults With Type 1 and Type 2 Diabetes

Abstract: OBJECTIVE -Hyperglycemia is a common event among patients with type 1 and type 2 diabetes. While the cognitive-motor slowing associated with hypoglycemia is well documented, the acute effects of hyperglycemia have not been studied extensively, despite patients' reports of negative effects. This study prospectively and objectively assessed the effects of hyperglycemia on cognitive-motor functioning in subjects' natural environment.RESEARCH DESIGN AND METHODS -Study 1 investigated 105 adults with type 1 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
162
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(181 citation statements)
references
References 23 publications
7
162
1
11
Order By: Relevance
“…Our results demonstrated that ecto-ADA activity was significantly increased in 111-mM glucose group, suggesting a decrease in adenosine levels in synaptic cleft. There is some consensus that a decrease of adenosine levels could be related with cognitive impairment observed in diabetic rats [8,55,56], which also could be suggested occurring in the zebrafish hyperglycemic model.…”
Section: Discussionmentioning
confidence: 98%
“…Our results demonstrated that ecto-ADA activity was significantly increased in 111-mM glucose group, suggesting a decrease in adenosine levels in synaptic cleft. There is some consensus that a decrease of adenosine levels could be related with cognitive impairment observed in diabetic rats [8,55,56], which also could be suggested occurring in the zebrafish hyperglycemic model.…”
Section: Discussionmentioning
confidence: 98%
“…However, the results of our study do not support the notion of any relationship between cognitive dysfunction and diabetic clinical characteristics. Whether variations in glucose homeostasis influence cognitive function remains controversial [49][50][51], although it has been found that the cognitive function of diabetic and nondiabetic subjects fluctuates in accordance with the serum glucose levels [50,51]. At the same time, increased insulin resistance is associated with atrophy of medial temporal lobe structures in elderly diabetic patients [52].…”
Section: Discussionmentioning
confidence: 99%
“…Evidências apontam para a relação positiva entre DM2 e declínio cognitivo, o qual também está implicado na inabilidade motora, devido ao comprometimento da atenção, da memória e de respostas protetoras, apraxia, desorientação espacial e deterioração das funções executivas e motoras (marcha alterada, desequilíbrio, instabilidade postural, alteração de tônus muscular); além do fato de os pacientes com essas condições não poderem julgar adequadamente sua própria capacidade, tomando atitudes arriscadas que levam a acidentes (7). Os défi-cits cognitivos, quando somados à presença de hiperglicemia, também podem aumentar a incapacidade física, trazendo dificuldades na realização de atividades da vida diária (AVD).…”
Section: Introductionunclassified
“…Entretanto, pouco se sabe sobre a relação entre distúrbio cognitivo e incapacidade física nos pacientes com DM2 (8). Estudos prévios sugerem que a alteração cognitivo-motora pode não apresentar uma relação linear com a glicemia, mas sim que pode haver um limite por volta de 270 mg/dL a partir do qual a função cognitivo-motora começaria a ser afetada (7). Embora se saiba a respeito da hipoglicemia e sua neuroglicopenia, um dos principais obstáculos para a investigação dos efeitos da hiperglicemia sobre o desempenho cognitivo-motor é a ausência de um mecanismo fisiológico claro que explique sua influência negativa sobre o funcionamento cerebral.…”
Section: Introductionunclassified